Plastic shopping bags: policy instruments for plastic bag reduction / Muhammad Hakim Noh - Noh, Muhammad Hakim (2013)
The plastic bag has become synonymous with our culture today. With almost 1 trillion plastic shopping bags consumed every year, their use is widespread, multifaceted, and convenient. However despite popularity, public concern over the current and future impacts of plastic shopping bags have been on the rise. Due to strong public pressure for government action, governments around the world are taking measures to address the issues associated with plastic bag use. To date, a number of countries have implemented plastic bag instruments which have succesfully reduced consumption and addressed impacts. On the other hand, a number of countries have also been mediocre or unsuccessful in signifcantly reducing consumption and impacts. This research provides an analysis of plastic bag policy instruments that can be used in order to assist policymakers in choosing an effective plastic bag policy. Each of the instruments is evaluated against social, environmental, and economic criteria, and is scored by the impacts and the expected outcomes. Plastic bag bans are stringent, costly to stakeholders, and are less likely to be publicly accepted. A levy on plastic bags are costly, but facilitates consumer choice and generates revenue. Lastly, while voluntary actions by retailers are inexpensive, they are weakly sanctioned and nominally reduce impacts. Analyzed against all criteria, this research suggests that the economic instrument, a plastic bag levy, is the most effective policy instrument for governments to address plastic shopping bags.